2011
DOI: 10.1097/fpc.0b013e3283424d94
|View full text |Cite
|
Sign up to set email alerts
|

Association study of the dopamine transporter gene with personality traits and major depressive disorder in the Han Chinese population

Abstract: Major depression is a complex psychiatric disorder involving multiple factors, including genetic and personality components. This study used 17 polymorphisms of dopamine transporter gene (DAT1) to explore whether this gene is associated with major depression and whether it influences personality traits in patients with major depression. The DAT1 polymorphisms were analyzed in 1017 unrelated individuals and 459 patients were eligible to assess personality traits. We found a borderline association between contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Using the model of Cloninger’s biosocial theory of personality, patients with AD have higher novelty seeking (NS) and harm avoidance (HA) scores than that found in controls [ 28 ]. Studies have found an association between the SLC6A3 gene and personality traits defined by the Cloninger’s model in healthy individuals [ 29 , 30 ] and patients with depression [ 31 ]. However, evidence demonstrating a relationship between the SLC6A3 gene and personality traits of Cloninger’s model in patients with AD remains lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Using the model of Cloninger’s biosocial theory of personality, patients with AD have higher novelty seeking (NS) and harm avoidance (HA) scores than that found in controls [ 28 ]. Studies have found an association between the SLC6A3 gene and personality traits defined by the Cloninger’s model in healthy individuals [ 29 , 30 ] and patients with depression [ 31 ]. However, evidence demonstrating a relationship between the SLC6A3 gene and personality traits of Cloninger’s model in patients with AD remains lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Dopamine is implicated in the regulation of specific personality traits [ 16 , 17 ], and dopamine transporter/receptor availability may also be associated with certain traits [ 18 , 19 ]. However, the relationship between DAT availability and personality has not been clearly established either among healthy subjects or patient populations [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The DAT1 gene was reported to effect personality traits in healthy controls (Kazantseva et al, 2011;Shibuya et al, 2009) and patients with mood disorder (Huang et al, 2011;Joyce et al, 2009), but there are no available data of personality-gene interactions in AD patients. The present study assessed the personality traits of AD patients using the Tridimensional Personality Questionnaire (TPQ) to determine whether specific personality and gene-personality interactions are involved in the pathogenesis of AD.…”
Section: Introductionmentioning
confidence: 99%